THE PUSH AND PULL MOTIVATIONAL FACTOR OF DESTINATION LOYALTY OF BUNAKEN ISLAND IN MANADO, NORTH SULAWESI - Rompas, Prince Syema; Tumbuan, Willem J. F. A.; Rumokoy, Farlane S. (FEB Universitas Sam Ratulangi Manado, 2018)
Abstract: Bunaken is an island of 8 kmÂ², part of the Bunaken National Marine Park. Bunaken is located at the northern tip of the island of Sulawesi, Indonesia.. Bunaken National Park extends over an area of 890.65 kmÂ² of which only 3% is terrestrial, including Bunaken Island, as well as the islands of Manado Tua, Mantehage, Nain and Siladen. Bunaken National Park can be reach through Manado Harbor, Marina Nusantara Diving Center (NDC) in Molas Subdistrict and Blue Banter Marina. From Manado Harbor by motor boat to Bunaken island + 30 minutes, from Blue Banter Marina by cruise ship for Bunaken Island can be reached within 10-15 minutes, while from NDC to dive site on Bunaken island by speed boat within + 20 minutes. This research used quantitaitve method. The sample of this research is 100 respondents. This research used purposive sampling and the date filled by the questionaire. The result of this research shows that the the independent variable which are push motivational factor and pull motivational factor simultaneously affect destination loyalty as the dependent variable, push motivational factor as one of independent variables does not partially affects destination loyalty significantly, pull motivational factor as one of independent variables does partially affects destination loyalty significantly. Recommendation is Bunaken Island should keep improving their local culture as a signature for people to come to their island and services such as resort and else that being open in bunaken island should keep develops to what the tourist needs because it will make tourist comes back again.Â Keywords: marketing,destination loyalty.